Letter of Appreciation to Our 2020 Reviewers in the Time of COVID‐19. Issue 4 (6th April 2021) - Xenopoulos, Marguerite A.; Goñi, Miguel; Desai, Ankur; Huntzinger, Deborah
Abstract: The editorial team at JGR: Biogeosciences would like to extend thanks to the 2020 reviewers who offered their time and expertize to help us make decisions on and improve papers. Key Point: We thank all 2020 reviewers for their contributions